AN OVERVIEW OF THE IMPLEMENTATION OF PRE-QUESTIONING STRATEGY IN TEACHING READING - Rusmiati, Rusmiati (Getsempena English Education Journal, 2014)
In reading, to comprehend the text the readers should be able to manage every part of the text, because it is easy to gain the comprehension in reading when the readers are able to organize the text. Sometimes, they may find form of pre-questioning and it is important for them to comprehend a reading text with having knowledge in general view of the text. Theoretically, pre-questioning itself can build the studentsâ interest and motivation before students read the whole text. Moreover, the students can predict what will be discussed on the text. In line with this study, students may improve their reading comprehension if they know about pre-questioning and it is very important to understand about pre-questioning in order to get good comprehension in reading. Based on the explanation above, it is interested to figure out an overview of the effect pre-questioning in teahing reading comprehension and to know the rule of pre-questioning that tends to build the studentsâ interest and motivation to read the text.Key words: Pre-questioning, Reading